FROM THE HISTORY OF LEARNING FRENCH - Mamasolieva Gulchexra Abdukhalilovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article gives a brief overview of the historical evolution of the French language. That is, a brief account of the historical processes of the formation of French as a language is given.